Purification, crystallization and initial crystallographic characterization of the Ginkgo biloba 11S seed globulin ginnacin - Jin, Tengchuan (International Union of Crystallography, 2008)
Ginkgo biloba, a well known ‘living fossil’ native to China, is grown worldwide as an ornamental shade plant. Medicinal and nutritional uses of G. biloba in Asia have a long history. However, ginkgo seed proteins have not been well studied at the biochemical and molecular level. In this study, the G. biloba 11S seed storage protein ginnacin was purified by sequential anion-exchange and gel-filtration chromatography. A crystallization screen was performed and well diffracting single crystals were obtained by the vapor-diffusion method. A molecular-replacement structural solution has been obtained. There are six protomers in an asymmetric unit. Structure refinement is currently in progress.